Тактика слідчого огляду під час розслідування викрадень природнього газу в газових лічильниках - Гусак, А.; Хомич, Д.; Husak, A.; Khomych, D. (Східноєвропейський національний університет імені Лесі Українки, 2018)
В статті висвітлено окремі організаційно-тактичні аспекти проведення огляду місця події. На підставі дослідження думок вчених, аналізу матеріалів слідчої практики визначено заходи з організації та проведення огляду місця події. Наведено тактичні прийоми, які найбільш доцільно використовувати при проведенні огляду місця події. Особливості підготовки та проведення огляду місця події у справах даної категорії пов’язані з необхідністю забезпечення участі спеціаліста в проведенні огляду; визначення переліку науково-технічних засобів, які використовуватимуться в ході огляду; забезпечення безпеки учасників огляду. The article highlights some organizational and tactical aspects of conducting inspection of the scene of the event. Measures for organizing and conducting inspection of the place of the event have been determined on the basis of scientists' opinions and materials of the investigative practice. The authors offer tactics that are most appropriate to use during the inspection of the scene and outlines tasks for inspecting the place of event in cases of stealing natural gas. The most actual among the tasks are: exposing the method of stealing gas through its unauthorized use; searching for and fixing traces that may indicate the perpetrator's identity. Preparation for the inspection of the scene of this category of offence implies specialist involvement into the inspection, guaranteeing the safety of the participants of the inspection, determining the list of scientific and technical means to be used. The key findings of the study contribute to clarifying the causes of poor-quality investigation of these crimes, one of which is the insufficient use of all possible facilities to inspect the place of the event. The organization, the order and tactical peculiarities of conducting this investigative action are considered in detail, taking into account the recommendations in the special literature.The authors worked out their own program/scheme for conducting an inspection of the place of the event.
Tactics of Investigative Inspection while Investigating the Cases of Natural Gas Stealing through Gas Meters
Keywords: слідчий огляд; місце події; спеціаліст; тактичний прийом; investigative inspection; place of the event; specialist; tactical methods